Combination therapy using plasmid DNA-mediated VP3 and SHCD147 genes for colon cancer in a murine model - Ismail, Ruzila (2014)
Several strategies have been pursued to develop cancer therapies that selectively act on and kill cancer cells preferentially, leaving normal cells unaffected. The VP3, an avian virus-derived protein, can specifically impulse the death signal to different signal transduction pathways and finally lead to the apoptosis of the host cancer cells. The present work utilized a stress-inducing promoter which is a glucoseregulated protein (GRP) promoter to enhance VP3 expression in solid tumor condition. On the other hand, the over-expression of Basigin/CD147, a transmembrane glycoprotein has association with malignant melanoma invasiveness, metastasis and angiogenesis. Since CD147 has been indicated to be one of the critical cell-surface proteins in promoting chemo-resistance and survivability of cancer stem cells (CSC), down regulation of its expression by RNAi is an attractive way to suppress CD147-dependent cell proliferation, invasion and metastatic activity of cancer cells to eventually induce anoikis. All necessary impact of efficiencies and in vitro evaluation to optimize in this project has been established. In this study, tumorbearing murine model was established. Investigation was conducted on 175-200 mm3 tumor model receiving highly purified plasmid DNA in single treatment or combination of VP3 and shCD147 via intratumoral route (n=8). An alternate-date dosing approach was practiced whenever 3 doses were needed. Control groups were either a) non-treated, b) received 3 doses of 100 μg of pVIVO1-GFP/LacZ or c) 3 doses of 100 μg of psiRNA-h7SKzeo. Whilst treated mice received either a) 3 doses of 100 μg of pVIVO1-GFP/VP3 or b) 3 doses of 100 μg of psiRNA-CD147. For combinative therapy, mice received either a) 3 doses of 50 μg of pVIVO1-GFP/VP3 with combination of 3 doses of 50 μg of psiRNA-CD147 or b) 3 doses of 100 μg of pVIVO1-GFP/VP3 plus 3 doses of 100 μg of psiRNA-CD147, as representative for low-dose and high-dose respectively. All the 56 mice were subjected to 12 h light/ 12 h dark cycle and kept in individually ventilated cages (IVC) with constant rotation rate of 70 air-changes/ h to ensure sterility. Administration of VP3 alone led to percentage tumor growth inhibition (TGI) of 40.0% and a 1.3-fold increase in the tumor growth delay index (TGDI) whilst administration of shCD147 led to TGI of 45.2% and 1.2-fold increase in the TGDI value. Whereas combination of low-dose treatment led to TGI of 51.1% (p<0.001) and a 2.0-fold increase in the TGDI whilst high-dose combinative treatment led to higher TGI of 60.3% (p<0.001) and 2.3-fold increase in the TGDI. These results demonstrated an extensive inhibition of CT26 tumor xenograft growth by VP3 and shCD147 combinative approach. Moreover,there is no discernible effect observed on histopathology and clinical chemistry profile of the host. The anti-proliferation and anti-angiogenic activities of the combinative approach were investigated by the use of the immunohistochemistry analysis, PCNA and vWF. Apoptotic cells were determined in the treated group by DNA fragmentation, TUNEL assay and confirmed by AnnV/PI double staining. The apoptosis percentage in the combinatively (VP3 + shCD14/2) treated tumor was markedly increased compared to individually treated samples at day-25 posttreatment. Here, it was found that CD147 silencing induced dual coordinated effects,resulting in inhibition of tumor cell proliferation and sensitization to VP3-induced apoptosis. In conclusion, this study showed that the combinative approach was more promising and effective in controlling tumor growth and inducing apoptosis than introducing VP3 or shCD147/2 alone. The combinative treatment also offers potential advantages in control of tumorigenesis, and thus deserves further research as a preferred approach in cancer gene therapy.